2017
DOI: 10.1590/s2175-97902017000215154
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of two separate analytical techniques for the simultaneous determination of diclofenac sodium and diacerein from combined dosage form

Abstract: Diclofenac sodium (DS) and diacerein (DC) have emerged as a potential combination therapy for the treatment of knee osteoarthritis. Therefore a validated analytical method is essential for the simultaneous estimation of both from combined dosage form. A ratio derivative spectrophotometric and a chromatographic technique have been developed for the simultaneous determination of DS and DC. The quantification was done at 263.00 nm for DC and 304.50 nm for DS in the first method, whereas 257 nm for DC and at 274 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Inter-person precision results were agreed with the findings of da Silva Santos et al, 31 who reported ruggedness RSD value at <5% during his research work on method validation of iron ion estimation. While investigating the efficacy of two separate analytical methods for simultaneous determination of DS and DC, Mallick et al 32 calculated the ruggedness value of 0.95% for DS and 0.96% for DC, showing the acceptability between the two methods.…”
Section: Resultsmentioning
confidence: 99%
“…Inter-person precision results were agreed with the findings of da Silva Santos et al, 31 who reported ruggedness RSD value at <5% during his research work on method validation of iron ion estimation. While investigating the efficacy of two separate analytical methods for simultaneous determination of DS and DC, Mallick et al 32 calculated the ruggedness value of 0.95% for DS and 0.96% for DC, showing the acceptability between the two methods.…”
Section: Resultsmentioning
confidence: 99%